Fetomaternal outcomes in eclamptic primigravida in a tertiary care centre - Nazida, Arham; Barman, Karabi; Das, Rajesh (International Journal of Research in Medical Sciences, 2023)
Background: As a tertiary care facility, our institute sees a high volume of complex pregnancy cases. The purpose of this study is to examine the foetal and maternal outcomes in primigravida cases with eclampsia, as they represent a high-risk but not uncommon patient subset in obstetric practice. Methods: This study was a prospective observational study of 80 primigravida patients admitted to the department of obstetrics and gynaecology, FAAMCH, Barpeta during the period of 4th September 2021 to 3rd September 2022. Maternal outcomes were studied in the mother and fetus, including pulmonary oooedema, placental abruption, HELLP syndrome, PPH, cerebral infarction, ICU admission, MODS, and stillbirth. Results: Pulmonary oedoema was the most common problem among the 80 subjects, with AKI, aspiration Pneumonitis, CVA, MODS, placental abruption, PPH, and HELLP syndrome. Only 14 subjects had to be admitted to the ICU, and 54 (67.50%) had no problems while they were still in the womb. Conclusions: This study found that most primigravida patients with eclampsia eventually underwent spontaneous vaginal delivery, with pulmonary oooedema being the most common maternal complication. Early intervention, such as blood pressure monitoring, and urine dipsticks, can influence the path of illness care for a patient. To reduce maternal and perinatal morbidity and mortality, good antenatal care is essential.